La teoría lógica de Franz Bolzano: una reacción contra el subjetivismo kantiano - Castrillo Criado, Pilar (ENDOXA, 2004)
Objectivism may be taken as a landmark of Atistrian philosophy. This tradition begins with Bemard Bolzano. Contrary to the Kantían picture of the working of the human mindas imposing its own structure on nature, Bolzano stresses the objectivity of our grasping the truth, thus íiberating cognition from the subjective constraints. To knotv something means always to know propositions as such. Bolzano ’s theory states that there are propositions in themselves which are the bearers of truth values and of logical relations